A re-examination of a human femur found at the Blind River Site, East London, South Africa: Its age, morphology, and breakage pattern - Wang, Qian; Tobias, Phillip V.; Roberts, David L.; Jacobs, Zenobia (Anthropological Review, 2008)
Modern human femoral features might have appeared in the early Middle Stone Age (156 ka to 20 ka) in South Africa, as demonstrated by the recent re-examination of a human femur fossil found at the Blind River Site, East London in the 1930s, if new dating results hold. Two optically stimulated luminescence dates from the relocated original Blind River shallow marine/estuarine deposits that contained the femur gave almost identical ages of ~120 ka, corresponding to the early part of the Last Interglacial (Oxygen Isotope Stage 5). Overall, the slender headless femur is of modern human form. The distal epiphysis bears some typical squatting features, including a newly recognized squatting facet on the anterior wall of the intercondylar fossa. With the typical V-shaped and oblique fracture pattern left by the missing head, the Blind River femur was most likely modified through human activity. But this style is not a cultural trait found in recent South African people. Further study is needed to place this specimen in its due context in the course of human evolution.